Inorganic gelling plugging agent and preparation method thereof
By using an inorganic gelling plugging agent combined with aluminum sulfate salt and silicate gelling material, combined with nanosilicon dioxide and other components, the problem of poor leakage plugging effect in the prior art is solved, and a moderate density is achieved Leak plugging agent has good temperature adaptability and compatibility, and can maintain the blocking effect under high pressure, solving the problem of leakage loss of leak slurry.
Patent Information
- Application Number
- CN202411198913.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art has poor results when sealing leaky strata such as cracks and caves, resulting in low leakage success rate, easy leakage slurry to leak, poor sealing effect, and poor compatibility with drilling fluid.
The inorganic gelling plugging agent is used to combine aluminum sulfate gelling material and silicate gelling material as the gelling base material, combined with water-soluble nano silica, diatomaceous earth, fly ash and other components, and then stirring and dry preparation to obtain a moderate density of leak plugging agent to improve the sealing effect.
It has achieved a wide temperature adaptation range, good stability, not easily eroded by water or drilling fluid, good compatibility and thixotropic properties, its density is similar to that of the leakage formation, it can gel quickly, achieve efficient sealing effect, and under high pressure Maintain blockage capability.
Smart Images

Figure BDA0005017313110000021 
Figure BDA0005017313110000022 
Figure BDA0005017313110000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas well plugging, in particular to an inorganic gelling plugging agent and a preparation method thereof. Background Art
[0002] With the continuous development of unconventional oil and gas resources, more and more complex leakage formations such as cracks and caves are encountered during drilling. The occurrence of lost circulation not only delays the operation time, loses drilling fluid, damages the oil and gas layer, and interferes with the logging work, but also may cause the well wall to become unstable, leading to complex accidents such as well collapse, drill stuck, blowout, and even wellbore scrapping, causing significant economic losses. It has become a common technical problem in the drilling process.
[0003] At present, the main plugging technologies for leaking formations such as fractures and caves include bridging plugging, cement plugging and polymer gelling plugging. In the bridging plugging method, due to the fragility or lack of skeleton of the rock, it is impossible to establish a stable plugging barrier and implement pressure plugging, resulting in an extremely low plugging success rate; in the cement plugging method, the density of cement slurry is much higher than the leakage pressure of fractures, caves and other formations, resulting in the cement slurry being easily leaked to the deep formation under the action of pressure difference, and the plugging effect cannot be achieved. Although the density of cement slurry can be reduced by increasing the water-cement ratio and adding a lightening agent, a large amount of water will be generated, and the volume will shrink severely after consolidation, resulting in the inability to effectively plug the leakage channel, making the plugging effect lower than expected; although the density of polymer gelling plugging slurry is similar to the pressure equivalent density of the leaking formation, it has poor compatibility with drilling fluid, and the formed cement blocks are easily eroded by formation fluids, resulting in poor plugging effect.
[0004] The Chinese invention patent "A controllable gelling plugging agent" (application number: 201610048849.5) discloses a controllable gelling plugging agent. The gelling plugging agent in the invention uses aluminum sulfate gel material with sulfonic acid group and organic chromium thixotropic coagulant, and is used in combination with polypropylene fiber, polyacrylamide stabilizer, sodium aluminate and barium oxide binder and organic silicon hydrophobic agent. Although the plugging agent has adjustable coagulation time, fast curing strength development, good thixotropic performance, water intrusion resistance, plugging strength and retention capacity, the minimum density of this plugging slurry is 1.40g / cm 3 , higher than the equivalent density of the lost formation pressure (0.95~1.20g / cm 3 ), will result in the plugging slurry having poor plugging effect on shallow leaking layers and weak retention capacity. It is easy to leak to deep formations under the action of pressure difference and cannot play a plugging role.
[0005] Therefore, how to provide a gelling plugging agent with good plugging effect is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0006] In view of this, the purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide an inorganic gelling plugging agent and a preparation method thereof for the poor effect of plugging agents in leaking formations such as cracks and caves.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] An inorganic gelling plugging agent, characterized in that the plugging agent is mainly composed of the following raw materials, measured by weight:
[0009]
[0010] Preferably, the plugging agent is mainly composed of the following raw materials, measured by weight:
[0011]
[0012] Preferably, the gelling base material is compounded by aluminum sulfate gelling material and silicate gelling material in a mass ratio of 1:(0.5-2.5).
[0013] Preferably, the slurry stabilizer is water-soluble nano-silicon dioxide with a particle size of 7-90 nm.
[0014] Preferably, the water-absorbing swelling agent is at least one of diatomaceous earth, calcium carbonate and water-absorbing resin.
[0015] Preferably, the density regulator is at least one of fly ash, buoyant beads and barite powder.
[0016] Another object of the present invention is to provide a method for preparing an inorganic gelling plugging agent which is simple to operate and suitable for large-scale production.
[0017] A method for preparing an inorganic gelling plugging agent, the method specifically comprising the following steps:
[0018] The inorganic gelling plugging agent is obtained by weighing the gelling base material, slurry stabilizer, water-absorbing swelling agent and density regulator according to the above disclosed weight proportions, stirring evenly, and then drying and cooling to room temperature.
[0019] Preferably, the stirring time is 2-4 hours, the drying temperature is 60° C.-80° C., and the drying time is 8-12 hours.
[0020] Specifically, the preparation method of the inorganic gelling plugging agent comprises the following steps:
[0021] Weigh a certain amount of gelling base material, slurry stabilizer, water-absorbing swelling agent and density regulator, place them in a stirrer and stir for 2-4 hours, place them in an oven, dry them at 60℃-80℃ for 8-12 hours, and cool them to room temperature to obtain an inorganic gelling plugging agent.
[0022] It can be seen from the above technical solution that, compared with the prior art, the present invention discloses an inorganic gelling plugging agent and a preparation method thereof, which has the following excellent effects:
[0023] 1. The temperature adaptability range of the plugging agent prepared by the present invention is 40°C-80°C, and it has good temperature adaptability;
[0024] 2. The plugging agent prepared by the present invention not only has good stability and will not be corroded by formation fluids such as water and drilling fluid, but also has good compatibility with polymer drilling fluid, polysulfone drilling fluid, salt-resistant drilling fluid, etc.;
[0025] 3. The plugging agent prepared by the present invention has strong thixotropic properties, does not gel under shearing conditions, can flow to the leakage layer, stops flowing after reaching the leakage layer, and quickly gels, achieving a good plugging effect;
[0026] 4. The plugging agent prepared by the present invention can be prepared into a low-density slurry, the density of which is close to the pressure equivalent density of the leaking formation, so that the slurry is easy to stay in the leaking formation, thereby achieving a better plugging effect;
[0027] 5. The gelling time of the plugging agent prepared by the present invention is adjustable, the solidification strength develops quickly, and the plugging capacity after solidification is higher than 5.0MPa. At the same time, the formed gel block can be partially acidified and can acidify the plugging formation. DETAILED DESCRIPTION
[0028] The technical solutions disclosed in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The embodiment of the invention discloses an inorganic gelled plugging agent with a plugging slurry density close to the equivalent density of the lost formation pressure and good plugging effect, and a preparation method thereof.
[0030] The inorganic gelling plugging agent is mainly composed of a gelling base material, a slurry stabilizer, a water-absorbing and swelling agent and a density regulator; the components include the following weight parts: 40-90 weight parts of the gelling base material, 4-11 weight parts of the slurry stabilizer, 4-10 weight parts of the water-absorbing and swelling agent, and 0-50 weight parts of the density regulator;
[0031] Further preferably, the plugging agent is mainly composed of the following raw materials, calculated by weight: 40-84 parts by weight of a gelling base, 5-10 parts by weight of a slurry stabilizer, 5-8 parts by weight of a water-absorbing swelling agent, and 0-40 parts by weight of a density regulator.
[0032] The gelling base material is compounded by aluminum sulfate gelling material and silicate gelling material in a mass ratio of 1:(0.5-2.5); preferably, the gelling base material is compounded by aluminum sulfate gelling material and silicate gelling material in a mass ratio of 1:(0.5-1.5).
[0033] The slurry stabilizer is water-soluble nano-silicon dioxide with a particle size of 7-90 nm; preferably, the particle size of the slurry stabilizer is 7-50 nm.
[0034] The water-absorbing swelling agent is one or a mixture of diatomaceous earth, calcium carbonate, and water-absorbing resin; preferably, the water-absorbing swelling agent is diatomaceous earth.
[0035] The density regulator is one or a mixture of fly ash, buoyant beads, and barite powder; preferably, the density regulator is compounded by buoyant beads and barite powder in a mass ratio of 1:(0.2-0.5).
[0036] The preparation method of the inorganic gelling plugging agent specifically comprises the following steps:
[0037] Weigh a certain amount of gelling base material, slurry stabilizer, water-absorbing swelling agent and density regulator, place them in a stirrer and stir for 2-4 hours, place them in an oven for drying for 8-12 hours, and cool them to room temperature to obtain an inorganic gelling plugging agent.
[0038] Wherein, the drying treatment temperature is 60-80°C; preferably, the drying treatment temperature is 70°C.
[0039] In the embodiment of the present invention, the inorganic gelling plugging agent provided by the present invention is added to water under stirring conditions to prepare a plugging slurry.
[0040] Wherein, the slurry preparation water is tap water or salt water; preferably, the slurry preparation water is tap water.
[0041] The stirring rate is 300-600 r / min, and the stirring time is 10-40 min; preferably, the stirring rate is 400-500 r / min, and the stirring time is 20-30 min.
[0042] The various substances selected as the above-mentioned additives can be commercially available products, or can be prepared according to conventional methods in the art, which will not be described in detail here.
[0043] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0044] The technical solution disclosed in the present invention will be further described below in conjunction with specific embodiments.
[0045] Embodiment 1:
[0046] A method for preparing an inorganic gelled plugging slurry comprises the following steps:
[0047] (1) Weigh 40 parts of aluminum sulfate gelling material, 42 parts of silicate gelling material, 10 parts of water-soluble nano-silicon dioxide, and 8 parts of diatomaceous earth by weight, stir them in a stirrer for 2 hours, place them in an oven for drying for 9 hours, and cool them to room temperature to prepare an inorganic gelling plugging agent A1.
[0048] (2) Weigh 96 g of plugging agent A1 and mix with 400 mL of water, and stir at a speed of 400 r / min for 20 min to prepare inorganic gel plugging slurry B1;
[0049] According to GB10238-2005 Oil Well Cement Standard, the density of plugging slurry B1 is 1.05g / cm 3 .
[0050] Example 2
[0051] A method for preparing an inorganic gelled plugging slurry comprises the following steps:
[0052] (1) Weigh 44 parts of aluminum sulfate gelling material, 32 parts of silicate gelling material, 8 parts of water-soluble nano-silicon dioxide, 8 parts of diatomaceous earth, 6 parts of floating beads and 2 parts of barite in parts by weight, stir them in a stirrer for 2 hours, place them in an oven for drying for 9 hours, and cool them to room temperature to obtain an inorganic gelling plugging agent A2.
[0053] (2) Weigh 96 g of plugging agent A2 and mix with 400 mL of water, and stir at a speed of 400 r / min for 25 min to prepare inorganic gel plugging slurry B2;
[0054] According to GB10238-2005 Oil Well Cement Standard, the density of plugging slurry B2 is 1.10g / cm 3 .
[0055] Example 3
[0056] A method for preparing an inorganic gelled plugging slurry comprises the following steps:
[0057] (1) 32 parts of aluminum sulfate gelling material, 32 parts of silicate gelling material, 10 parts of water-soluble nano-silicon dioxide, 6 parts of diatomaceous earth, 14 parts of floating beads and 6 parts of barite were weighed in parts by weight, stirred in a stirrer for 2 hours, placed in an oven for drying for 9 hours, and cooled to room temperature to obtain an inorganic gelling plugging agent A3.
[0058] (2) Weigh 96 g of plugging agent A3 and 400 mL of water, mix them, and stir at a speed of 450 r / min for 30 min to prepare inorganic gel plugging slurry B3;
[0059] According to GB10238-2005 Oil Well Cement Standard, the density of plugging slurry B3 is 1.20g / cm 3 .
[0060] Example 4
[0061] A method for preparing an inorganic gelled plugging slurry comprises the following steps:
[0062] (1) 30 parts of aluminum sulfate gelling material, 17 parts of silicate gelling material, 5 parts of water-soluble nano-silicon dioxide, 8 parts of diatomaceous earth, 28 parts of floating beads and 12 parts of barite were weighed in parts by weight, stirred in a stirrer for 2 hours, placed in an oven for drying for 9 hours, and cooled to room temperature to obtain an inorganic gelling plugging agent A4.
[0063] (2) Weigh 96 g of plugging agent A4 and mix with 400 mL of water, and stir at a speed of 500 r / min for 30 min to prepare inorganic gel plugging slurry B4;
[0064] According to GB10238-2005 Oil Well Cement Standard, the density of plugging slurry B4 is 1.30g / cm 3 .
[0065] The content of the present invention is not limited to the content of the above embodiments. The combination of one or more embodiments can also achieve the purpose of the present invention.
[0066] In order to verify the excellent effect of the inorganic gelling plugging agent disclosed in the present invention, the inventors also conducted the following experiments:
[0067] Test Example 1:
[0068] The rheological properties of the plugging slurries B1-B4 in Examples 1-4 were tested according to the standard GB / T29170-2012 "Drilling Fluid Laboratory Test". The test results are shown in Table 1.
[0069] Table 1
[0070]
[0071] From the rheological properties test results of the plugging slurry in Table 1, it can be seen that the dynamic plastic ratio of the plugging slurries B1-B4 prepared in Examples 1-4 is higher than 0.3, indicating that the plugging slurries B1-B4 will not gel under stirring and have excellent rheological properties. Among them, the apparent viscosity, plastic viscosity, and dynamic shear force of the plugging slurry B4 are the largest. This is because as the amount of density regulator increases, the solid content in the plugging slurry increases, which increases the apparent viscosity, plastic viscosity, and dynamic shear force of the slurry, but the dynamic plastic ratio changes little, and it still has good fluidity.
[0072] Test Example 2:
[0073] The plugging slurries B1-B4 in Examples 1-4 were placed at different temperatures, and the gelling time of the plugging slurries B1-B4 was tested according to the GB10238-2005 "Oil Well Cement" standard. At the same time, the compressive strength of the plugging slurries B1-B4 after gelling for 8 hours was tested according to the GB / T19139-2012 "Test Methods for Oil Well Cement" standard. The test results are shown in Table 2.
[0074] Table 2
[0075]
[0076]
[0077] From the results of gelling time and compressive strength of plugging slurry in Table 2, it can be seen that as the temperature increases, the gelling time of plugging slurries B1-B4 prepared in Examples 1-4 becomes shorter and the compressive strength increases. Among them, the gelling time and compressive strength of plugging slurry B1 prepared in Example 1 are better than those of plugging slurries B2-B4 prepared in Examples 2-4. This may be due to the reduction of cement addition and the increase of density adjustment dosage. When the temperature is higher than 40°C, the compressive strength of the four plugging slurries is greater than 3MPa, which meets the plugging requirements.
[0078] Test Example 3
[0079] The plugging pressure bearing capacity of the plugging slurries B1-B4 in Examples 1-4 was tested using a simulated sandstone formation test device. The specific test method is as follows: 20-40 mesh quartz sand is loaded into a sand filling pipe to simulate high permeability sandstone. The channel in the sand filling pipe is first filled with 2% brine to measure the initial permeability. The plugging slurries B1-B4 are then injected into the sand filling pipe. After they are fully gelled at 60°C, a replacement experiment is carried out with brine to record the change in the rate of leakage and calculate the brine permeability after plugging. The test results are shown in Table 3.
[0080] Table 3
[0081]
[0082] From the changes in brine permeability before and after plugging of plugging slurries B1-B4 in Table 3, it can be seen that when the pressure is lower than the compressive strength of the gel blocks B1-B4, the permeability gradually decreases with the increase of pressure, indicating that the plugging slurry has good plugging ability, while when the pressure is higher than its compressive strength, the gel blocks are prone to cracks, resulting in poor plugging effect.
[0083] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An inorganic gelling plugging agent, characterized in that: The plugging agent is mainly composed of the following raw materials, measured by weight:
2. An inorganic gelling plugging agent according to claim 1, characterized in that: The plugging agent is mainly composed of the following raw materials, measured by weight:
3. An inorganic gelling plugging agent according to claim 1, characterized in that: The gelling base material is compounded by mixing aluminum sulfate gelling material and silicate gelling material in a mass ratio of 1:(0.5-2.5).
4. An inorganic gelling plugging agent according to claim 1, characterized in that: The slurry stabilizer is water-soluble nano silicon dioxide with a particle size of 7-90 nm.
5. An inorganic gelling plugging agent according to claim 1, characterized in that: The water-absorbing swelling agent is at least one of diatomaceous earth, calcium carbonate and water-absorbing resin.
6. The inorganic gelling plugging agent according to claim 1, characterized in that: The density regulator is at least one of fly ash, floating beads and barite powder.
7. A method for preparing the inorganic gelling plugging agent according to any one of claims 1 to 6, characterized in that: The method specifically comprises the following steps: The inorganic gelling plugging agent is obtained by weighing the gelling base material, slurry stabilizer, water-absorbing swelling agent and density regulator according to the weight proportions as claimed in claim 1, stirring evenly, and then drying and cooling to room temperature.
8. The method for preparing an inorganic gelling plugging agent according to claim 7, characterized in that: The stirring time is 2-4 hours, the drying temperature is 60° C.-80° C., and the drying time is 8-12 hours.
